Youth Digital Participation: Now More than Ever - Kligler-Vilenchik, Neta (2020)
One of the far-reaching implications of the current global COVID-19 pandemic has been the sudden boost in use of digital media due to social distancing and stay-at-home orders. In times of routine, youth are often the first to adopt new technologies and platforms, to experiment with modes of production and practices of sharing, and often spend significant time and energy socializing online. Now such digital practices have become common among much wider demographics. Moreover, the move to online learning in schools and the spurt of innovative digital experiences offered has abruptly shifted the rhetoric of concern often associated with youth’s so-called “screen time.” The articles in this thematic issue—though written long before the COVID-19 pandemic—address many of the questions that now are significantly brought to the forefront. What are the potentials and opportunities offered by youth digital participation for learning, for self-expression, for identity formation, and for social connection? How does digital participation shape civic and political life? And finally, especially when digital participation is so ever-present, what are barriers to youth participation online, and what are the challenges and risks it poses?